A Primer on Ebola for Clinicians. (17th October 2014) - Toner, Eric; Adalja, Amesh; Inglesby, Thomas
Abstract: The size of the world's largest Ebola outbreak now ongoing in West Africa makes clear that further exportation of Ebola virus disease to other parts of the world will remain a real possibility for the indefinite future. Clinicians outside of West Africa, particularly those who work in emergency medicine, critical care, infectious diseases, and infection control, should be familiar with the fundamentals of Ebola virus disease, including its diagnosis, treatment, and control. In this article we provide basic information on the Ebola virus and its epidemiology and microbiology. We also describe previous outbreaks and draw comparisons to the current outbreak with a focus on the public health measures that have controlled past outbreaks. We review the pathophysiology and clinical features of the disease, highlighting diagnosis, treatment, and hospital infection control issues that are relevant to practicing clinicians. We reference official guidance and point out where important uncertainty or controversy exists. ( Disaster Med Public Health Preparedness . 2014;0:1-5)